Pawpaws prevent predictability: A locally dominant tree alters understory beta‐diversity and community assembly - Anna C. Wassel; Jonathan A. Myers (Ecosphere)
Abstract While dominant species are known to be important in ecosystem functioning and community assembly, biodiversity responses to the presence of dominant species can be highly variable. Dominant species can increase the importance of deterministic community assembly by competitively excluding species in a consistent way across local communities, resulting in low site‐to‐site variation in community composition (beta‐diversity) and nonrandom community structure. In contrast, dominant species could increase the importance of stochastic community assembly by reducing the total number of individuals in local communities (community size), resulting in high beta‐diversity and more random community structure. We tested these hypotheses in a large, temperate oak‐hickory forest plot containing a locally dominant tree species, pawpaw (Asimina triloba; Annonaceae), an understory tree species that occurs in dense, clonal patches in forests throughout the east‐central United States. We determined how the presence of pawpaw influences local species diversity, community size, and beta‐diversity by measuring the abundance of all vascular plant species in 1 × 1‐m plots both inside and outside pawpaw patches. To test whether the presence of pawpaw influences local assembly processes, we compared observed patterns of beta‐diversity inside and outside patches to a null model in which communities were assembled at random with respect to species identity. We found lower local species diversity, lower community size, and higher observed beta‐diversity inside pawpaw patches than outside pawpaw patches. Moreover, standardized effect sizes of beta‐diversity from the null model were lower inside pawpaw patches than outside pawpaw patches, indicating more random species composition inside pawpaw patches. Together these results suggest that pawpaw increases the importance of stochastic relative to deterministic community assembly at local scales, likely by decreasing overall numbers of individuals and increasing random local extinctions inside patches. Our findings provide insights into the ecological processes by which locally dominant tree species shape the assembly and diversity of understory plant communities at different spatial scales.